Phospholipid Adsorption Polymeric Materials for Detection of Xylazine and Metabolite in Blood and Urine - Xue Gao; Hao Guo; Chaokang Gu (International Journal of Polymer Science)
Polymers have been used in different areas. Recently, polymeric material is favored in analytical area due to its high performance and high consistency, which was used in sample pretreatment in this study. Xylazine poisoning is often seen in body fluid samples obtained from various accidents or suicides. However, the content of xylazine is difficult to detect precisely due to matrix effect in testing practices. In this paper, a method application for phospholipid adsorption polymeric materials to determine xylazine in blood and urine samples was proposed, developed, and validated. Compared with existing method, this method using polymeric pretreatment has a wider linear range of 2.0–2000.0 ng/mL for xylazine and its metabolite 2,6-dimethylaniline in both blood and urine and lower detection limits of 0.3 ng/mL for 2,6-dimethylaniline and xylazine in blood and 0.2 ng/mL for 2,6-dimethylaniline and xylazine in urine. Therefore, this method is suggested to be applied in testing practices by academic groups and commercial organizations.